IMPLEMENTASI MANAJEMEN PEMBIAYAAN DI SMAN 8 KEDIRI : ANALISIS PERENCANAAN, PENCAIRAN, PELAKSANAAN DAN EVALUASI PEMBIAYAAN - Siska Yulia Weny; Refi Nur Fadila; Lela Fitria Sari; Baihaqy Abdullah (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2024)
This research aims to analyze the implementation of Financing Management at SMAN 8 Kediri using a qualitative approach. The main focus of the research covers four important aspects in management, namely planning, budget disbursement process, budget implementation and evaluation. The methods used in this research include interviews with various stakeholders and analysis of related documentation. The research results show that the HR planning process at SMAN 8 Kediri was carried out systematically by considering the school's short-term and long-term needs. Planning and preparing the budget prioritizes urgent and important matters in accordance with the Technical Guidelines. Sources of funds come from BOS and BPOPP which are used for school operational activities. Even though there are still several obstacles or obstacles in budgeting, such as increasing market prices or non-implementation of activities, SMAN 8 Kediri regularly evaluates in order to minimize failures or deficiencies in activities.